2011
DOI: 10.5194/acp-11-5045-2011
|View full text |Cite
|
Sign up to set email alerts
|

Middle atmosphere response to the solar cycle in irradiance and ionizing particle precipitation

Abstract: Abstract. The impact of NO x and HO x production by three types of energetic particle precipitation (EPP), auroral zone medium and high energy electrons, solar proton events and galactic cosmic rays on the middle atmosphere is examined using a chemistry climate model. This process study uses ensemble simulations forced by transient EPP derived from observations with one-year repeating sea surface temperatures and fixed chemical boundary conditions for cases with and without solar cycle in irradiance. Our model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 109 publications
10
75
0
Order By: Relevance
“…[41] The All SC HA p and HS-HA p stratospheric polar temperature response, with a warming signal in the upper stratosphere and a cooling signal below at high latitudes in January-February, is very similar to those predicted by Baumgaertner et al [2011] and Semeniuk et al [2011] as a seasonal mean temperature response to enhanced EPP. Based on earlier work by others, Baumgaertner et al [2011] suggested that the warming signal would be a result in decrease in ozone radiative cooling as a response to ozone depletion, and the cooling signal might arise from dynamical heating due to slowing down of the meridional BrewerDobson circulation.…”
Section: Discussionsupporting
confidence: 55%
“…[41] The All SC HA p and HS-HA p stratospheric polar temperature response, with a warming signal in the upper stratosphere and a cooling signal below at high latitudes in January-February, is very similar to those predicted by Baumgaertner et al [2011] and Semeniuk et al [2011] as a seasonal mean temperature response to enhanced EPP. Based on earlier work by others, Baumgaertner et al [2011] suggested that the warming signal would be a result in decrease in ozone radiative cooling as a response to ozone depletion, and the cooling signal might arise from dynamical heating due to slowing down of the meridional BrewerDobson circulation.…”
Section: Discussionsupporting
confidence: 55%
“…Odd nitrogen, produced by precipitating electrons, is longlived during polar winter and can then be transported down from its source region into the stratosphere, to altitudes well below 30 km. This has been postulated already by Solomon et al (1982) and observed many times (Callis et al, 1996;Stratospheric ozone loss due to electron-induced NO x production in the upper mesosphere-lower thermosphere and subsequent downward transport has been postulated by model experiments many times (Solomon et al, 1982;Schmidt et al, 2006;Marsh et al, 2007;Baumgaertner et al, 2009;Reddmann et al, 2010;Semeniuk et al, 2011;Rozanov et al, 2012). However, observational evidence for EPP-induced variations of stratospheric ozone linked to geomagnetic activity, characterized by a negative anomaly moving down with time during polar winter, have been given only very recently (Fytterer et al, 2015a;Damiani et al, 2016).…”
Section: Geomagnetic Forcing (Auroral and Radiation Belt Electrons)mentioning
confidence: 94%
“…A further step would be to include SSI variability in the radiation calculation. This would allow to evaluate the importance of these two levels of feed-back on the ozone response to solar variability and results could be compared with Semeniuk et al (2011) and Gruzdev et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…We chose the Equator, where dynamical effects on ozone are smallest, to make our experiments more (although not entirely) comparable to CCMs. The initial concentrations and temperature are set to monthly and zonally averaged values taken from a 22-yr simulation with the Canadian Middle Atmosphere Model (Semeniuk et al, 2011) with greenhouse gases and halogen concentrations fixed to year 1979 (courtesy Kirill Semeniuk). Initial concentrations of longlived species are taken constant with altitude and are listed in Table 1.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation